Spatio-Temporal Modification of Lignin Biosynthesis in Plants: A Promising Strategy for Lignocellulose Improvement and Lignin Valorization - Wang, Yongli; Gui, Cunjin; Wu, Jiangyan; Gao, Xing; Huang, Ting; Cui, Fengjie; Liu, Huan; Sethupathy, Sivasamy (Frontiers in Bioengineering and Biotechnology, 2022)
Lignin is essential for plant growth, structural integrity, biotic/abiotic stress resistance, and water transport. Besides, lignin constitutes 10–30% of lignocellulosic biomass and is difficult to utilize for biofuel production. Over the past few decades, extensive research has uncovered numerous metabolic pathways and genes involved in lignin biosynthesis, several of which have been highlighted as the primary targets for genetic manipulation. However, direct manipulation of lignin biosynthesis is often associated with unexpected abnormalities in plant growth and development for unknown causes, thus limiting the usefulness of genetic engineering for biomass production and utilization. Recent advances in understanding the complex regulatory mechanisms of lignin biosynthesis have revealed new avenues for spatial and temporal modification of lignin in lignocellulosic plants that avoid growth abnormalities. This review explores recent work on utilizing specific transcriptional regulators to modify lignin biosynthesis at both tissue and cellular levels, focusing on using specific promoters paired with functional or regulatory genes to precisely control lignin synthesis and achieve biomass production with desired properties. Further advances in designing more appropriate promoters and other regulators will increase our capacity to modulate lignin content and structure in plants, thus setting the stage for high-value utilization of lignin in the future.